Evaluating Modified Tannin Esters as Functional Additives in Polypropylene and Biodegradable Aliphatic Polyester. Issue 10 (16th May 2014) - Grigsby, Warren J.; Bridson, James H.; Lomas, Cole; Frey, Helena
<x xml:space="preserve">Abstract</x> Esterified and native condensed tannins have been evaluated in polypropylene and the aliphatic polyester Bionolle. Tannin esters at typical plastic additive loadings have minimal effect on plastic mechanical properties. In assessing functional equivalence tannin esters inhibit the effects of UV degradation in both polypropylene and Bionolle with tannin hexanoate acetate having greater efficacy than a synthetic UV stabiliser at comparable loading. Oxidative induction testing also suggests the tannin esters can act to prevent oxidative degradation of polypropylene. However, retention of antioxidant capacity was crucial to inhibiting oxidative degradation. Outcomes suggest bio‐based tannin additives have potential to substitute synthetic additives and improve plastic sustainability credentials.<inline-graphic xlink:href="ark:/27927/pgh1fd1530z" content-type="mame201400051-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />